RANCANG BANGUN SISTEM INFORMASI PENGGAJIAN KARYAWAN ADREENA VILLAGE CILEUNGSI - Fahrizal; Rio Rakapratama (JURNAL LENTERA ICT, 2023)
The problem that occurred in the company was that data management was still using a manual system, making it difficult for Adeeena Village to manage and store data. Therefore, a data management application was created to manage employee payroll more effectively, quickly, and accurately. The system developed is a web-based application, while the programming used is Framework, PHP, and Javascript, with a MySQL database. The results of this research are structured sales data, so this system can also maximize work efficiency. This system can be further developed in the future to further improve the employee payroll system.